THE EVOLUTION OF CHINA'S STRATEGIC INTERESTS IN CENTRAL ASIA - Dilnura Allaberganova (International Journal of Literature and Language Studies, 2026)
This thesis examines the evolution of the People's Republic of China's strategic interests in Central Asia from geopolitical, geoeconomic, and security perspectives. The study explores how China's regional policy has transformed in the post-Cold War period, evolving from a security-oriented approach to a broader strategy aimed at economic integration and the expansion of geopolitical influence. Particular attention is paid to the Belt and Road Initiative (BRI), energy cooperation, and transportation and communication projects as key instruments of China's regional engagement. The findings demonstrate that China's policy toward Central Asia is multidimensional and guided by long-term strategic objectives.